Development of optical transceiver - Tang, Hongbo. (2010)
The world of optical data communication now is well established and continues to thrive. Mature technologies conbined with high-volume, low-cost manufacing have made high performance optical data links more affordable than ever before and have turned some of the early technologies into commodities. Optcial component prices have come down dramatically as volumes have increased and manufacturing technology has improved. Therefore, thre is a great need to integrate photonics with standard electronic integrated circuit in order to combine the information processing capabilities of IC and the benefits of optical communications. Silicon technology has the potential to provide low-cost, reliable solutions with the performance that will be required for short-distance communications systems. A silicon-based approach to transmitters and receivers appears promising. The design, fabrication, and characterization can be realized compatibly with the current Si technology.